2007
DOI: 10.3390/medicina43120128
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary arterial hypertension

Abstract: Plaučių arterinė hipertenzija yra grupė ligų, kurioms būdingas progresuojantis spaudimo plaučių arterijoje didėjimas, sąlygojantis dešiniojo skilvelio nepakankamumą ir priešlaikinę mirtį.Plaučių arterinė hipertenzija nustatoma, kai vidurinis spaudimas plaučių arterijoje ramybės metu didesnis nei 25 mmHg, fizinio krūvio metu didesnis nei 30 mmHg. Spaudimo plaučių arterijoje padidėjimas susijęs su padidėjusiu plaučių kraujagyslių pasipriešinimu. Pleištinis slėgis plaučių kapiliaruose ir galinis diastolinis spaud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…19,21,22 It is reported that more than 80 Canadians die annually from overexposure to the cold, whereas 8000 die of hypothermia-related causes. 24,25 Although data are scarce concerning the pediatric population, a study from the US Armed Forces reported that soldiers younger than 20 years are at increased risk. 26…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…19,21,22 It is reported that more than 80 Canadians die annually from overexposure to the cold, whereas 8000 die of hypothermia-related causes. 24,25 Although data are scarce concerning the pediatric population, a study from the US Armed Forces reported that soldiers younger than 20 years are at increased risk. 26…”
Section: Definition and Epidemiologymentioning
confidence: 99%
“…2,3 When convulsions occur in addition to these signs of preeclampsia, the condition is referred to as eclampsia. 4,5 Preeclampsia is primarily a disorder of nulliparous, but multiparous pregnant women with a new partner have an elevated risk of preeclampsia like that of nulliparous women. 6 Preeclampsia complicates 10% of all pregnancies; it was found that 3-5% of first pregnancies and 1% of subsequent pregnancies are complicated by preeclampsia.…”
Section: Introductionmentioning
confidence: 99%
“…Pulmonary arterial hypertension (PAH) is a chronic debilitating cardiopulmonary disease characterized by abnormal remodeling of peripheral lung vasculature resulting in progressive vasoconstriction [1]. PAH is associated with an elevated pulmonary arterial pressure (> 25 mm Hg at rest to > 30 mm Hg with exercise) and if left untreated leads to right-heart hypertrophy, and consequently heart failure [2].PAH could be classified as idiopathic (formerly known as primary pulmonary hypertension) or associated with autoimmune, infectious, vascular, metabolic, and congenital disorders [1].The underlying pathology of PAH involves the recruitment of inflammatory cells with release of cytokines which enhance cell proliferation and elastin fibers degradation [3]. Histologically, PAH is characterized by intimal fibrosis, increased medial thickness, predominance of complex plexiform lesions resulting in vasoconstriction and pulmonary arteriolar occlusion [4].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, in IPF, treatment is mainly geared towards relieving symptoms as much as possible and slowing down the progression. The prognosis ofPAH and IPF is poor [1,6], hence, there is a clear necessity to develop new therapies.…”
Section: Introductionmentioning
confidence: 99%